YO’L QOPLAMALARI UCHUN BETONLARNING OPTIMAL TARKIBI ISHLAB CHIQISH: YEVROPA DAVLATLARI MISOLIDA - Botirova Nodira Sherali qizi, Ergasheva Baxora Baxodir qizi, Sharifov Xayitmurod Odin o’g’li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article is dedicated to the development of optimal concrete composition for road pavements and the study of European experience. Within the framework of the article, various types of concrete and their characteristics used in European countries are analyzed. The process of developing an optimal composition and the possibilities for adapting European standards and technologies to local conditions are also discussed. The consideration of ecological aspects and the use of innovative materials are of significant importance. The research findings provide recommendations aimed at improving the quality of road pavements and enhancing economic factors.